Synthesis and characterization of Fe3O4/rGO/Ag composites for electrocatalytic oxygen reduction reaction (ORR) - Komaty Maran; Sarah Ilyanie Roswadi; Mohd Afifi Jusoh; Farhanini Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2025)
The oxygen reduction reaction (ORR) plays a pivotal role in fuel cells, making the discovery of efficient and cost-effective catalysts to substitute platinum crucial for the progress of sustainable energy technologies. This study investigates a new rGO/Fe3 O4 /Ag composite as a potential low-cost substitute for platinum-based cathode materials in ORR applications due to platinum’s drawbacks. Reduced graphene oxide incorporated with iron (III) oxide and silver nanoparticles were synthesized through a modified one-pot process, denoted as rGO/Fe3 O4 /Ag. This study is the first to utilize rGO/Fe3 O4 / Ag as an ORR catalyst. Synthesis began with the formation of graphene oxide, followed by its reduction, the addition of Fe2+ and Fe3+, and the introduction of silver nanoparticles via silver nitrate (AgNO3 ) to produce the novel electrocatalyst. Physicochemical and electrochemical characterization was performed using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), Brunauer-Emmett-Teller (BET) analysis, and cyclic voltammetry (CV). FTIR confirmed the presence of functional groups such as O-H, C=C, C=O, C-O, C-Fe, and C-Ag in the nanocomposites. XRD identified average crystalline sizes, with diffraction peaks confirming the formation of rGO/Fe3 O4 /Ag. SEM-EDX analysis showed well-dispersed Fe3 O4 and Ag nanoparticles on rGO sheets, and BET analysis indicated the nanocomposites were mesoporous, with a surface area of 81.60 m2 /g for rGO/Fe3 O4 /Ag. Electrochemical characterization showed that the modified rGO/Fe3 O4 /Ag exhibited significant redox responses, indicating enhanced electrochemical activity compared to the bare GCE. In the ORR analysis, the rGO/Fe3 O4 /Ag demonstrated a positive shift in the cyclic voltammogram, suggesting improved current density and superior ORR performance relative to the bare GCE. These results strongly suggest that rGO/Fe3 O4 /Ag can be an effective replacement for platinum in ORR applications as a cathode material. Keywords: Cyclic voltammetry; electrocatalyst; graphene; iron oxide; oxygen reduction reaction (ORR)